Light Intensity Influence on Growth and Photosynthetic Characteristics of Horsfieldia hainanensis - Wang, Xin; Chen, Guode; Du, Shangjia; Wu, Haixia; Fu, Rong; Yu, Xuebiao (Frontiers in Ecology and Evolution, 2021)
Due to both anthropogenic and natural causes, the number of Horsfieldia hainanensis has been decreasing each year in the Tongza Branch nursery (109.534 525°E, 18.763 516°N) of the Hainan Academy of Forestry, China. Consequently, the protection of H. hainanensis is urgent, as is that of most rare tree species. To develop a more comprehensive understanding of the H. hainanensis growth environment, we took 3-year-old H. hainanensis saplings as the research object. We controlled the light intensity by setting different shade amounts to explore the growth and photosynthetic characteristics of H. hainanensis under different light intensities. We found that shade can promote growth and increase the contents of certain substances. Light transmittance of 44.41% can increase plant height (by 29.545%) and biomass (by 66.676%). Light transmittance of 16.19% can increase the pigment content; Chl increased by 40.864%, Chl a increased by 38.031%, and Chl b increased by 48.412%. Light transmittance of 7.30% can increase the soil plant analysis development (SPAD) value of each part of the leaf; the leaf base increased by 41.000%, the leaf margin increased by 32.574%, the blade tip increased by 49.003%, and the leaf average increased by 40.466%. The specific leaf area can reduce the specific leaf weight. We also found that compared to full light, reducing the light transmittance can increase the total chlorophyll (Chl), chlorophyll A (Chl a), and chlorophyll B (Chl b) contents, and the Chl-SPAD-leaf base, leaf edge, leaf tip, average content, and light-saturated net photosynthetic rate. This can in turn reduce the apparent quantum efficiency (AQY), light compensation point (LCP), and dark respiration rate (Rd). In addition, we found a strong correlation between seven of the photosynthetic pigment indicators (Chl, Chla, Chl b, Chl-SPAD-leaf base, leaf margin, leaf tip, and mean) and the three photosynthesis physiological parameters (AQY, LCP, and Rd). The light transmittance of 44.41% (one layer of shading net) treatment group was conducive to the growth of H. hainanensis and photosynthetic characteristic improvement. Therefore, our light transmittance selection of approximately 44.4% is significant for the natural return of H. hainanensis.